Aplicaci?n de M?todos Multicriterio para la Selecci?n de Materiales para Menaje de Cocinas de Inducci?n - Mart?nez G?mez, Javier (2015)
This investigation shows results about materials selection for pans of induction cookers, which takes into account the interplay between the requirements of design, materials and product processing. It has identified physical properties, as well as, restrictions on the health, appearance, material and processing cost. Finally, it has studied the ability to adapt manufacturing processes by industry in Ecuador. As a result, it has established the candidate materials which meet the above requirements. This is the case of AISI 430 or electromagnetic steel, as well as materials typically used for induction utensils. Finally, it was used different selection models like Pugh, Dominic and Pahl - Beitz methods, which allowed choosing the best materials for the process. The results have shown that there are three settings as candidate materials: a) Stainless steel AISI 430 or AISI 436, AISI 304 steel and Teflon non-stick coating inside, b) AISI 430 or AISI 436 stainless steel which has been inlaid in an aluminum pan and c) Cast iron with vitrified treatment.